Pendampingan Pengelolaan Keuangan Keluarga pada Pengrajin Anyaman Pandan - Eva Malina Simatupang; Arlina Pratiwi Purba; Nurlinda Nurlinda; Angelia Maharani Purba; Mardelia Desfrida (Lembaga Pengembangan Kinerja Dosen, 2026)
This community service activity aimed to improve financial literacy and family financial management skills based on priority scales among housewives in the pandan mat weaving artisan community in Sei Balai District, Batubara Regency, North Sumatra Province. The main problems faced by the community partners included limited understanding of simple financial record-keeping, the absence of separation between business and household finances, and low saving habits due to fluctuating income levels. The implementation method employed a participatory approach through observation, lectures, interactive discussions, household budgeting practices, and simple financial recording training. The results of the activity indicated that participants experienced an improvement in their understanding of the importance of distinguishing between needs and wants, arranging expenditure priorities, and developing saving habits as well as preparing family emergency funds. In addition, participants also began to recognize the importance of financial record-keeping as an effort to control household expenditures more effectively and efficiently. The participants’ enthusiasm throughout the program demonstrated that the materials delivered were highly relevant to community needs. Therefore, this outreach activity contributed positively to enhancing family financial management capabilities and supporting the economic well-being of the pandan mat weaving artisan community.